STRATEGI PENGUATAN IDENTITAS SISWA MELALUI REKONSTRUKSI PAI DI ERA DIGITAL - Andi Hidayat (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The background of the study is based on the high intensity of technology and digital media use among adolescents, which has implications for the formation of their religious, moral, and social identities. In this context, PAI has a strategic role in guiding students to be able to use technology responsibly and in harmony with Islamic values. This study uses a descriptive qualitative approach with the main subjects being PAI teachers, students, and school management. Data were collected through observation, interviews, and documentation of the planning, implementation, and evaluation of PAI learning integrated with the use of digital media. The results of the study indicate that PAI reconstruction was carried out through curriculum adjustments and learning plans that integrate classical Islamic themes with contemporary issues in the digital space, innovations in problem-based and project-based learning methods, and the utilization of various digital media and online platforms. The strategy for strengthening student identity is implemented through digital reflection and self-reflection, religious habituation, and empowering students to actively participate in producing Islamic religious content and positive activities in digital media. These efforts contribute to increasing students' awareness, selective attitudes, and moral responsibility in using technology, despite still facing challenges such as teachers' digital competence, limited resources, and the influence of the external environment.